2020
DOI: 10.1080/19420862.2020.1829333
|View full text |Cite
|
Sign up to set email alerts
|

On-column disulfide bond formation of monoclonal antibodies during Protein A chromatography eliminates low molecular weight species and rescues reduced antibodies

Abstract: Disulfide bond reduction, which commonly occurs during monoclonal antibody (mAb) manufacturing processes, can result in a drug substance with high levels of low molecular weight (LMW) species that may fail release specifications because the drug’s safety and the efficiency may be affected by the presence of this material. We previously studied disulfide reoxidation of mAbs and demonstrated that disulfide bonds could be reformed from the reduced antibody via redox reactions under an optimal redox condition on P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Furthermore, this case study demonstrated that the redox wash has no negative impact on process yield or product quality. Extensive characterization of the reoxidized antibody confirmed a complete formation of interchain disulfide bonds and comparable biophysical properties to the reference material (Tan et al, 2020).…”
Section: Case Study On Disulfide Bond Reduction Elimination and Disulfide Reduced Mab Recoverymentioning
confidence: 59%
See 4 more Smart Citations
“…Furthermore, this case study demonstrated that the redox wash has no negative impact on process yield or product quality. Extensive characterization of the reoxidized antibody confirmed a complete formation of interchain disulfide bonds and comparable biophysical properties to the reference material (Tan et al, 2020).…”
Section: Case Study On Disulfide Bond Reduction Elimination and Disulfide Reduced Mab Recoverymentioning
confidence: 59%
“…Comprehensive evaluation using redox wash system in the platform Protein A chromatography (Tan et al, 2020). The study was performed using three mAb harvest cell cultures according to the design including three arms.…”
Section: Case Study On Disulfide Bond Reduction Elimination and Disulfide Reduced Mab Recoverymentioning
confidence: 99%
See 3 more Smart Citations